Pelatihan Vokasi Bagi Narapidana Reintegrasi oleh Pokmaslipas di Bapas Purwokerto - Lalu Harjan Islamianto; Ihsanudin Ihsanudin; Kholil Lur Rochman (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2025)
This study aims to explore the role of Community Groups Caring for Corrections (Pokmas Lipas) in empowering former employees at Bapas Purwokerto. Former employees face complex challenges during reintegration into society, including negative stigma, limited skills, and access to resources. Through a qualitative approach, this study identified various programs run by Pokmas, such as skills, moral support training, and provision of facilities to help former employees re-adapt. The results of the study indicate that Pokmas Lipas plays an important role in reducing community stigma, building self-confidence, and creating a more inclusive environment. With the right support, former participants can function productively and responsibly in society, thereby reducing the risk of recidivism. This study is expected to provide insights and strategic steps to improve the effectiveness of previous empowerment programs in the future.